Endoscopic needle bladder neck suspension for female stress incontinence - Hara, M (Hinyokika kiyo. Acta urologica Japonica, 1989)
Thirteen operations of endoscopic bladder neck suspension (Raz method) were performed for 12 patients with stress incontinence between October, 1986 and August, 1988. In all patients, except for one with small bladder capacity, the operations were successful. Disappearance of incontinence was maintained in 10 patients 5-27 months (mean 15.3 months) after the operation, and the success rate of this operation was 77% (10/13) at this follow up point. The operative technique was easy except for the adjustment of pulling up strength of the thread for suspension. We believe that the endoscopic needle bladder neck suspension will be performed more widely because this operation can be done safely in a short time without major complications and can produce very good results